Marketing - A.Kerin Roger (Mc Graw Hill, 2010)
Marketing 10/e by Kerin, Hartley and Rudelius continues a tradition of leading the market with contemporary, cutting-edge content presented in a conversational student-oriented style, supported by the most comprehensive, innovative, and useful supplement package available. This text and package is designed to meet the needs of a wide spectrum of faculty—from the professor who just wants a good textbook and a few key supplements, to the professor who wants a top-notch fully integrated multimedia program.